DEVELOPMENT OF THE WAY OF REDUCTION OF ATMOSPHERIC MOISTURE ABSORPTION OF THE SEMICONDUCTORS, PREPARED TO METALLURGICAL PROCESSING - A. S. Panasjugin; S. L. Rimoshevskij; S. V. Grigorjev; D. P. Mikhalap (Литьë и металлургия)
The aim of the present article is development of the way of atmosphere moisture absorption decrease by prepared to metallurgical processing with copper-containing galvanoslags.